Cytotoxicity of Ethyl Acetate Extract of Avocado Seeds (Persea americana Mill.) on Mouse Melanoma B16F10 Cell Line - Sebayang, Shalina; Mariya, Silmi; Rayendra, Raendi; Wientarsih, Ietje; Priosoeryanto, Bambang Pontjo (HAYATI Journal of Biosciences, 2025)
Artificial whitening agents available in the market can cause damage to melanocytes; therefore, a safe and naturally derived skin-whitening agent is needed. Avocado seeds (Persea americana Mill.) are often discarded as waste but possess numerous health benefits. One of the compounds in avocado seeds is catechin, a flavonoid metabolite. This compound has been reported to exhibit antioxidant activity and inhibit tyrosinase to prevent melanin formation, making it suitable for skin-whitening applications. This study aimed to conduct phytochemical screening, assess antioxidant activity using the DPPH method, analyze catechin content using HPLC, and perform cell viability tests using the MTT method from the ethyl acetate extract of avocado seeds. Phytochemical screening has revealed the presence of flavonoids, saponins, and steroids. The DPPH assay yielded an IC50 value of 89.47±0.73 ppm, indicating an intense antioxidant activity, and HPLC detected 0.09% catechin. The MTT test results yielded cell viability percentages ranging from 80-100% at test concentrations of 0.75-25 ppm, with an IC50 value of 61.7 ppm. In conclusion, our results indicate that the ethyl acetate extract from avocado seeds affects cell viability without toxicity, warranting further testing for tyrosinase inhibition in the mouse melanoma B16F10 cell line.